2018
DOI: 10.1016/j.icarus.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Regional stratigraphy of the south polar layered deposits (Promethei Lingula, Mars): “Discontinuity-bounded” units in images and radargrams

Abstract: The Mars South Polar Layered Deposits (SPLD) are the result of depositional and erosional events, which are marked by different stratigraphic sequences and erosional surfaces. To unambiguously define the stratigraphic units at regional scale, we mapped the SPLD on the basis of observed discontinuities (i.e., unconformities, correlative discontinuities and conformities), as commonly done in terrestrial modern stratigraphy. This methodology is defined as “Discontinuity-Bounded Units” or allostratigraphy, and is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Fig. 11(d) displays a depth map of the regional discontinuity (named here as AUR1) which is converted from the AUR1 DTM produced by Guallini et al (2018). According their study, the AUR1 should correspond to the SS2 shown in Fig.…”
Section: The 3-d Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…Fig. 11(d) displays a depth map of the regional discontinuity (named here as AUR1) which is converted from the AUR1 DTM produced by Guallini et al (2018). According their study, the AUR1 should correspond to the SS2 shown in Fig.…”
Section: The 3-d Processingmentioning
confidence: 99%
“…Three sequences of layered deposits have been identified in this region. Between the top and the second layer sequences, an angular unconformity has been revealed by analysing high-resolution surface images (Kolb and Tanaka, 2006) and from analysing manually SHARAD radargrams Milkovich et al, 2009;Guallini et al, 2018). Although layer exposures can be found extending the South Polar Layered Deposits (SPLD) in the surface images, such as from Mars Orbital Camera (MOC) and Thermal Emission Imaging System (THEMIS) images, the extent of these layer sequences is observed to be interrupted in the SHARAD radargrams.…”
Section: Study Site and Datamentioning
confidence: 99%
See 3 more Smart Citations